Exploring English Teachers’ Perceptions of U-Shaped Seating Arrangements in Enhancing Collaborative Learning - Syahruni, Syahruni; Radhiyani, Fitri; Arham, Muhammad (Pascasarjana Universitas Negeri Makassar, 2025)
The objectives of this study are 1) to find out how U-shaped seating arrangements can enhance collaborative learning, 2) to find out how teachers perceive U-shaped seating arrangements in enhancing collaborative learning. This study was motivated by the fact that many teachers still use traditional seating arrangements, which make learning monotonous and ineffective due to the lack of innovation in classroom management. This study is a qualitative descriptive study with data collection techniques in the form of observation using field notes and interviews. The participants in this study were students in grades IX A and IX B and two English teachers at SMP Negeri 2 Barombong, who were selected using purposive sampling. Observations were conducted in grades IX A and IX B to explore how U-shaped seating arrangements could enhance collaborative learning. The results of the observation showed that U-shaped seating arrangements can enhance collaborative learning because they facilitate interaction between students, help teachers monitor individual responsibilities, support the development of communication skills through open discussion, and create space for students to share knowledge more easily. In addition, this layout also makes it easier for teachers to act as mediators in classroom interactions, even though it still presents some challenges in its implementation. The interviews with two English teachers showed that teachers perceive the U-shaped seating arrangement as facilitating student interaction and engagement, encouraging the development of communication skills in collaborative learning, helping teachers control the class and student performance, and making it easier for students to share knowledge. However, teachers also acknowledged the challenges in implementing this model and provided solutions to overcome them. Based on the results of the study, it can be concluded that U-shaped seating arrangements can enhance collaborative learning while providing opportunities and challenges for teachers in classroom management. These findings emphasize the importance of classroom physical design as a classroom management strategy to create more effective collaborative learning.